1998
DOI: 10.1111/j.1474-919x.1998.tb04392.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intra‐specific dominance relationships and feeding behaviour of Golden Eagles Aquila chrysaetos and Sea Eagles Haliatetus albicilla at carcasses

Abstract: The behaviour of Golden Eagles Aquila chrysaetos and Sea Eagles Haliceetus albicilla scavenging on artificially laid out carcasses in coastal Sør‐Trøndelag Province, Norway, was studied during two winters (totalling 640 h of observations) and the intervening summer (430 h). Neither species fed at carcasses in summer. Although smaller, Golden Eagles were strongly dominant over Sea Eagles in direct competition for carcass access. In Sea Eagles, females dominated males, while in Golden Eagles, few conflicts betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Our finding that bald eagles were lead poisoned more frequently than golden eagles could be the result of golden eagles being more successful predators and less likely to feed on carrion containing lead fragments, or bald eagle carcasses being noticed more frequently, because of the white plumage on adults, than golden eagle carcasses. Displacement of golden eagles scavenging on lead-containing carcasses by bald eagles seems unlikely because of the aggressive nature of golden eagles (Halley and Gjershaug 1998). We also found that female eagles were diagnosed with lead poisoning more frequently that males and adults more frequently than juveniles.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our finding that bald eagles were lead poisoned more frequently than golden eagles could be the result of golden eagles being more successful predators and less likely to feed on carrion containing lead fragments, or bald eagle carcasses being noticed more frequently, because of the white plumage on adults, than golden eagle carcasses. Displacement of golden eagles scavenging on lead-containing carcasses by bald eagles seems unlikely because of the aggressive nature of golden eagles (Halley and Gjershaug 1998). We also found that female eagles were diagnosed with lead poisoning more frequently that males and adults more frequently than juveniles.…”
Section: Discussionmentioning
confidence: 86%
“…We also found that female eagles were diagnosed with lead poisoning more frequently that males and adults more frequently than juveniles. This may be at least partially explained by intraspecific dominance at scavenged carcasses, although there is more evidence for females displacing males than for adults displacing juveniles (Halley and Gjershaug 1998;Garcelon 1990). In combined data from two reports of lead poisoning in bald eagles, 18 of 26 birds were females and 14 of 26 were adults (Kaiser et al 1980;Reichel et al 1984).…”
Section: Discussionmentioning
confidence: 92%
“…IUCN guidelines also recommend monitoring the effect, if any, of reintroductions on the established native flora and fauna. Golden Eagles are dominant over White-tailed Eagles in Norway (Halley & Gjershaug 1998). Nevertheless, the possibility that Whitetailed Eagles reintroduced to Scotland might outcompete resident Golden Eagles (Watson 1997, Halley 1998 has not been entirely ruled out, in spite of substantial evidence to the contrary (Whitfield et al 2002, Love 2003, Evans et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if competition occurs in Scotland, and reintroduced White-tailed Eagles are to displace Golden Eagles (Thom 1986, Watson et al 1992, Watson 1997, Halley & Gjershaug 1998, Halley 1998, the limiting resource is most likely to be food, and White-tailed Eagles should be the superior competitor. Halley & Gjershaug (1998) showed that the Golden Eagle is the superior interference competitor over food, based on observations of behavioural interactions at carcasses in Norway. This runs counter to the postulated competitive advantage of reintroduced White-tailed Eagles over Golden Eagles.…”
mentioning
confidence: 99%
“…Since their reintroduction to western Scotland in 1975 numbers of White-tailed Eagles have been increasing (Green et al 1996, Evans et al 2003, 2009). Several authors have suggested that the continued spread of the White-tailed Eagle in Scotland will lead to displacement of Golden Eagles through competitive effects as coastal ranges are reclaimed (Thom 1986, Watson et al 1992, Watson 1997, Halley & Gjershaug 1998, Halley 1998.…”
mentioning
confidence: 99%